Effectiveness of exposure therapy on anxiety and sensory over-responsivity among children with autism spectrum disorder - Ms. K. ALLI, M.O.T,; Ms. B.S. SANMATHI PRIYA, B.O.T, (International Journal of Pharma and Bio Sciences, 2017)
To evaluate the effectiveness of Exposure Therapy (in vivo) on anxiety and sensory over responsivity among children with Autism Spectrum Disorder. This study is to assess the effectiveness of Exposure Therapy (in vivo) on anxiety and sensory over responsivity among children with Autism Spectrum Disorder. A Quasi quantitative experimental design, conducted at various settings such as Pebbles- Centre for child development, Commissionerate for the welfare of differently abled and finally in Pediatric unit, SRM University, Ramapuram with 26 Autism Spectrum Disorder Children of the age group 3- 10 years assessed using Sensory Profile and Hamilton Anxiety Rating Scale. The outcome of the study shows significant improvement in reducing sensory over responsivity and anxiety among children with Autism Spectrum Disorder. The results were obtained through an observation, parental interview, assessment tools and Wilcoxon signed rank test through SPSS trial version 20.0 with alpha level set at 0.05 was used for statistical anal in sample population. The result of this study suggest that exposing children to their feared sensory stimulus reduces their sensory over-responsivity and anxiety regarding that stimulus. Exposure therapy (in vivo) helped the children to reduce sensory over responsivity and anxiety related to it. Exposure therapy (in vivo) will be effective in reducing sensory over responsivity and anxiety related to it among children with Autism Spectrum Disorder.